2010
DOI: 10.1093/mutage/geq045
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and repair activity after broccoli intake in young healthy smokers

Abstract: Cruciferous vegetables contain compounds with antioxidant properties (e.g. carotenoids, vitamin C and folates) and can alter the activity of xenobiotic metabolism (i.e. isothiocyanates). These constituents may be particularly important for subjects who are exposed to free radicals and genotoxic compounds, including smokers. The aim of the study was to evaluate the effect of broccoli intake on biomarkers of DNA damage and repair. Twenty-seven young healthy smokers consumed a portion of steamed broccoli (250 g/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 34 publications
1
39
1
1
Order By: Relevance
“…Increases in OGG1 activity were reported after coenzyme Q 10 [59], slow-release vitamin C (but not conventional vitamin C capsules) [60], carrots (but not carotenes, vitamin C or mandarin oranges) [58], kiwifruit [61] and a high fruit and vegetable diet [62]. There was no effect of broccoli [63], or a cocktail of Se, retinol, b-carotene, vitamin C and vitamin E [64]. After folate supplementation, surprisingly, a decrease was seen, but only in individuals who were relatively folate-deficient [65].…”
Section: Animal Studies Of the Effect Of Micronutrients On Dna Repairmentioning
confidence: 95%
See 2 more Smart Citations
“…Increases in OGG1 activity were reported after coenzyme Q 10 [59], slow-release vitamin C (but not conventional vitamin C capsules) [60], carrots (but not carotenes, vitamin C or mandarin oranges) [58], kiwifruit [61] and a high fruit and vegetable diet [62]. There was no effect of broccoli [63], or a cocktail of Se, retinol, b-carotene, vitamin C and vitamin E [64]. After folate supplementation, surprisingly, a decrease was seen, but only in individuals who were relatively folate-deficient [65].…”
Section: Animal Studies Of the Effect Of Micronutrients On Dna Repairmentioning
confidence: 95%
“…This is generally found to be very slow, taking up to 24 h to [63] complete, compared with the rapid rejoining seen in most cultured cells [11,55]. Supplementation with vitamin C [56], b-carotene, lycopene (but not lutein) [57] or carrots [58] apparently accelerated the rejoining process.…”
Section: Animal Studies Of the Effect Of Micronutrients On Dna Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in BER was reported with slow-release vitamin C capsules in a 4-week placebo-controlled trial (Guarnieri et al, 2008). There was no significant effect of intervention with a mix of selenium, retinol, β-carotene, vitamin C, and vitamin E for 6 weeks (Caple et al, 2010), nor after a broccoli-rich diet for 10 days in a crossover trial (Riso et al, 2010). A diet rich in fruits and vegetables (600 g/day) resulted in no effect on BER (Guarnieri et al, 2008), whereas a similar study of the effects of antioxidant-rich fruits and vegetables (Brevik et al, 2011b) showed a significant increase in BER (and a smaller, non-significant increase with three green kiwifruits/day).…”
Section: Studies Using the Comet-based In Vitro Dna Repair Assaymentioning
confidence: 99%
“…The study was placebo-controlled, with a 20-day washout period between placebo-and broccoli-diet interventions. Blood was taken before and after both intervention periods, providing four DNA samples per volunteer over a period of about 6 weeks (study details in [58]). All 12 DNA samples were analyzed on one 450k bead chip, thus avoiding problems associated with batch affects.…”
Section: Illumina 27k and 450k Beadchip Arraysmentioning
confidence: 99%